라이프라인 시스템 상호의존성을 고려한 기능 저하 평가 및 복구계획 분석 - 이슬비; 박문서; 이현수; 황성주; Lee, Seulbi; Park, Moonseo; Lee, Hyun-Soo; Hwang, Sungjoo (한국건설관리학회 논문집, 15(4), 2014)
Lifeline service disruptions can have significant impacts on local community in the aftermath natural disaster. Although effective restoration strategies with accurate damage assessment are required, the internal complexity of lifeline networks and their interdependency makes the understanding restoration process of lifeline systems a difficult issue. Additionally, the limitations of previous research relating the influence assessment of lifeline to community disaster resilience, highlight the need for understanding of lifeline networks. Therefore, this paper presents an agent-based model to discover emergent behavior and evaluate the interdependency and resiliency in lifeline networks. This research will provide basic guideline of resource allocation in order to mitigate cascading failures of the post disaster restoration processes. 재난 이후 라이프라인의 손상은 지역사회 내 공공서비스의 제공을 지연시켜 서비스를 필요로 하는 시설물로 피해를 확산시킬 수 있다. 이에 라이프라인의 정확한 피해 평가를 기반으로 한 신속한 라이프라인의 복구가 요구되고 있으나, 라이프라인 구성요소간의 복잡한 의존관계와 네트워크적 성격으로 인해 복구계획을 수립하는데 어려움이 따른다. 또한 라이프라인의 위험도 평가 및 영향력 분석과 같은 기존의 연구들 역시 라이프라인 구성요소 간의 상호작용을 확인하기에는 한계가 있다. 따라서 본 연구에서는 에이전트 기반 모델을 활용하여 라이프라인 구성요소가 전체 네트워크시스템에 발현하는 연쇄피해효과를 확인하고, 라이프라인 간 상호의존성을 고려한 라이프라인 기능회복 모델을 제시하고자 한다. 이를 통해 전체 네트워크에 파급효과가 큰 라이프라인 구성요소에 우선적으로 복구 자원을 할당할 수 있도록 지원하여, 라이프라인 서비스 공급 중단으로 인한 지역사회의 피해확산을 경감시킬 수 있을 것이라 기대된다.